Evaluation of alternatives for Penicillium digitatum imazalil resistant strains postharvest management - Lado, Joanna; Luque, Eleana; Blanco, Oribe; Pérez Faggiani, Elena (Agrociencia Uruguay, 2011)
The control of Green mold caused by Penicillium digitatum in Uruguayan packinghouses is based in imazalil (IMZ) application. As a result, resistant strains appeared. The aim of this work was to evaluate different alternatives for postharvest control of IMZ resistant (1.0 mg l-1 in vitro) P. digitatum strains. Valencia and Ellendale fruit were inoculated with P. digitatum S22 (IMZ sensitive) and R20 (IMZ resistant) strains. Afterwards, they were treated by a 15 s immersion in IMZ, pyrimethanil (PYR) or fludioxonil (FLU) alone or combined with salts: sodium bicarbonate (BCS), sodium carbonate (CS) or potassium sorbate (SP). After 15 days of storage at 20 ± 2 ºC pathogen incidence was registered. For Ellendale, IMZ was the best fungicide for sensitive strain management, achieving 100% control with 500 mg l-1. Although disease incidence was lower than 25% with 500 μL l-1 PYR or FLU application, control efficacy was lower than for IMZ treatment. For resistant strain PYR and FLU were as effective as IMZ (1500 mg l-1), with 80% of healthy fruit. BCS applied at 1, 2 or 3% reduced pathogen incidence, being significantly superior in mixture with IMZ 500 mg l-1. For Valencia oranges an incidence reduction higher than 90% was obtained by IMZ 1500 mg l-1 and IMZ + PYR 750 μL l-1. These alternatives reveal that is possible to develop anti-resistance strategies for P. digitatum IMZ resistant strains management.